Ответ: 1) -3(а+b+2)=-3*a+(-3)*b+(-3)*2=-3a-3b-6
2) 3(2-a)=-3a+6
6a-3a+3a=6
6a=6
a=6/6
a=1
3) a) 2(x+4)-5=2x+8-5=2x+3
b) 3(y-1)-8=3y-3-8=3y-11
4) a) 15+(a+b)=15+a+b
b) 6-(c-d)=6-c+d
5) a) (20+x)+10=20+x+10=30+x
b) 30-(x+3)=30-x-3=27-x
![Ответ: 1) -3(а+b+2)=-3*a+(-3)*b+(-3)*2=-3a-3b-62) 3(2-a)=-3a+66a-3a+3a=66a=6a=6/6a=13) a) 2(x+4)-5=2x+8-5=2x+3 b) 3(y-1)-8=3y-3-8=3y-114) a) 15+(a+b)=15+a+b b) 6-(c-d)=6-c+d5) a) (20+x)+10=20+x+10=30+x b) 30-(x+3)=30-x-3=27-x Ответ: 1) -3(а+b+2)=-3*a+(-3)*b+(-3)*2=-3a-3b-62) 3(2-a)=-3a+66a-3a+3a=66a=6a=6/6a=13) a) 2(x+4)-5=2x+8-5=2x+3 b) 3(y-1)-8=3y-3-8=3y-114) a) 15+(a+b)=15+a+b b) 6-(c-d)=6-c+d5) a) (20+x)+10=20+x+10=30+x b) 30-(x+3)=30-x-3=27-x](https://tex.z-dn.net/?f=%D0%9E%D1%82%D0%B2%D0%B5%D1%82%3A%201%29%20-3%28%D0%B0%2Bb%2B2%29%3D-3%2Aa%2B%28-3%29%2Ab%2B%28-3%29%2A2%3D-3a-3b-62%29%203%282-a%29%3D-3a%2B66a-3a%2B3a%3D66a%3D6a%3D6%2F6a%3D13%29%20a%29%202%28x%2B4%29-5%3D2x%2B8-5%3D2x%2B3%20%20%20%20b%29%203%28y-1%29-8%3D3y-3-8%3D3y-114%29%20a%29%2015%2B%28a%2Bb%29%3D15%2Ba%2Bb%20%20%20b%29%206-%28c-d%29%3D6-c%2Bd5%29%20a%29%20%2820%2Bx%29%2B10%3D20%2Bx%2B10%3D30%2Bx%20%20%20%20b%29%2030-%28x%2B3%29%3D30-x-3%3D27-x)
Пошаговое объяснение: